2018
DOI: 10.1037/fam0000403
|View full text |Cite
|
Sign up to set email alerts
|

Financial stress response profiles and psychosocial functioning in low-income parents.

Abstract: Parenting in the context of poverty is accompanied by heightened stress and heightened stakes. How parents respond to poverty-related stress has important implications for family functioning, but research investigating individual differences in low-income mothers' and fathers' responses to financial stress and their associations with parents' concurrent psychosocial adaptation is lacking. A better understanding of differences in stress responses among low-income parents is required to develop and tailor preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 56 publications
3
14
0
1
Order By: Relevance
“…Profiles differed in meaningful and informative ways on measures of gender but not age. Inactive Copers were more likely than members of other coping profiles to be boys; a result that is consistent with previous study findings that adolescent ( Herres 2015 ) and adult ( Perzow et al 2018 ) men endorse less coping behavior than women do. Alternatively, previous research has also found gender differences in adolescent perceived stress, with girls endorsing higher stress than boys ( Hampel and Petermann 2005 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Profiles differed in meaningful and informative ways on measures of gender but not age. Inactive Copers were more likely than members of other coping profiles to be boys; a result that is consistent with previous study findings that adolescent ( Herres 2015 ) and adult ( Perzow et al 2018 ) men endorse less coping behavior than women do. Alternatively, previous research has also found gender differences in adolescent perceived stress, with girls endorsing higher stress than boys ( Hampel and Petermann 2005 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have also consistently identified a profile of adolescents characterized by active, approach, or engagement strategies comparable to the Engaged Copers ( Aldridge and Roesch 2008 ; Herres 2015 ; Okafor et al 2016 ; Seiffge-Krenke and Klessinger 2000 ). The profiles identified in the sample of low-SES adolescents were also generally similar to profiles of stress responses identified in a sample of racially diverse, low-SES parents using the RSQ ( Perzow et al 2018 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Person-centered approaches, such as latent profile analysis (LPA; Gibson, 1959) and cluster analysis, have provided critical, new information about coping in samples facing elevated stress. For example, Perzow et al (2018) examined financial stress responses in a sample of lowincome parents and identified five profiles of coping that were differentially related to mental health. Other studies that examined coping profiles in high-stress samples include examinations of young adults at risk for substance abuse (Wong et al, 2013), adults experiencing high levels of work-related stress (Astvik & Melin, 2013), and older chronically ill patients (Stecz, Wrzesinska, Tabala, & Nowakowska-Domagala, 2017).…”
Section: Person-centered Coping Profiles Moderate the Links Between Racial Discrimination And Mental Health In Black Americansmentioning
confidence: 99%
“…Numerous studies, both within and outside the family stress model framework, have linked economic hardship, material hardship, or financial strain to caregivers’ mental health, psychological well-being, or emotional distress (Masarik & Conger, 2017; Perzow et al, 2018). Psychological or affective responses including depressive mood (Rigotti et al, 2014), life satisfaction (Bruns & Pilkauskas, 2019), and more general psychological distress including generalized anxiety disorder (Benach et al, 2014) have been linked to conditions of employment such as job insecurity, involuntary job loss, multiple job holding, and temporary or otherwise contingent employment.…”
Section: Literature Reviewmentioning
confidence: 99%